CAMPUR KODE DALAM PERTUTURAN MASYARAKAT ETNIK CINA DI GANG BARU SEMARANG (Code Mixing in the Utterances of Chinese Ethnic Community in Gang Baru Semarang) - NFN Sutarsih (Balai Bahasa Sulawesi Selatan, 2017)
Code mixing occurs in the utterances of Chinese ethnic community in Gang Baru Semarang. The purpose of this research is describing code mixing in utterances of Chinese ethnic community in Gang Baru Semarang and describing the cause of code mixing in the utterances of Chinese ethnic community in Gang Baru Semarang by using functional descriptive method. Data analyzed as functional descriptive by using contextual method (context situational approach) in the utterances of Chinese ethnic community in Gang Baru. The result shows that code mixing occurs in the level of word based on the diction and suffix from Javanese, Chinese, and English. Code mixing in English is done by those who have backgrounds from modern school. Code mixing of Javanese and Chinese is done by them who have high social relationship with different ethnic community. The cause of code mixing is the speaker adapts with the partner’s language.AbstrakCampur kode terjadi pada masyarakat etnik Tionghoa di Gang Baru Semarang. Campur kode dalam bahasa tutur masyarakat tersebut terjadi pada tataran kata karena pilihan kata dari bahasa Jawa, akhiran yang berasal dari tata bahasa bahasa Jawa, bahasa Mandarin, dan bahasa Ingris. Campur kode bahasa Inggris dilakukan oleh mereka yang berlatar belakang keluarga berpendidikan tinggi di sekolah modern. Campur kode bahasa Jawa, Mandarin, dan Arab dilakukan oleh mereka yang menjalin hubungan sosial yang sangat tinggi dengan masyarakat berbeda etnik di lingkungan.